Acute bacterial encephalitis complicated with recurrent nasopharyngeal carcinoma associated with Elizabethkingia miricola infection: A case report - Zhuo, Xiaohuang; Zhou, Yongzhao; Liu, Ling (Frontiers in Neurology, 2023)
Elizabethkingia miricola (E. miricola) is an extremely rare pathogenic bacterium, that causes serious infections in patients with primary immunodeficiency or tumors, and it is often misdiagnosed. E. miricola has been rarely known to cause a neurologic infection. We describe the first case of acute bacterial encephalitis associated with E. miricola infection in a man with recurrent nasopharyngeal carcinoma which was successfully cured by antibiotics. The patient initially presented with recurrent episodes of fever and later showed impaired consciousness but these symptoms were alleviated with antibiotic therapy including cefoperazone/sulbactam. This study highlights that rapid and accurate pathogen detection via metagenomic next-generation sequencing and early use of appropriate antibiotics can improve the prognosis of patients with suspected neurologic E. miricola infection. Early treatment for underlying primary diseases can also significantly improve the outcomes of patients.